PERKEMBANGAN FINANCIAL TECHNOLOGI (FINTECH) BERDASARKAN PERSPEKTIF EKONOMI ISLAM - Hendra Kusuma; Wiwiek Kusumaning Asmoro (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2020)
This research is a library research. The method used in this research is Library Research or literature review, which collects data from literature and other sources that support and are related to the discussion of this study. The results of this study are: (1) There are 5 major roles of Start- up Financial Technology, namely, First financial transactions become more practical and safer. Second, it can advance the development of bitcoin. Third, it can improve people's lives. Fourth, it can build banking infrastructure as a solution to increase people's purchasing power. Fifth, can remove loan sharks. (2) The relevance of Financial Technology in today's development, it is very clear that its relationship in the daily life of the community, which provides convenience for the needs of the community in conducting financial transactions, such as payments, buying and selling of shares, borrowing and other transactions through technology. (3) Financial Technology is not contradictory to the Islamic economic system as long as it follows the legal principles of a contract, and meets the conditions and principles as well as the applicable law.